Analysis of Service Effectiveness on Customer Satisfaction in the Food & Beverage Bussiness in Tarutung, North Tapanuli - North Sumatra - Nugraha, Syahrul; Supraoto, Yon; Masditou (International Journal of Economics and Management, 2024)
The aim of this research is to determine the impact of service towards the consumer satisfaction, and the use of digital technology in service operations in the food and beverage business in Tarutung, North Tapanuli. The data processing techniques were obtained through distributing questionnaires to 80 respondents. The data analysis technique used is simple regression analysis. The research shows that a). physical appearance variables have a significant negative effect on consumer satisfaction; the reliability variable has an insignificant positive effect on consumer satisfaction; the responsiveness variable has a negative/insignificant effect on consumer satisfaction; the concern variable has a negative/insignificant effect on consumer satisfaction; and the guarantee variable has a significant effect on consumer satisfaction. The variables that have a dominant influence are the physical appearance variable and the guarantee variable which has a significant influence on consumer satisfaction. This means that service effectiveness (reliability, response has a positive and significant effect on consumer or customer satisfaction in the food and beverage business "is proven empirically and is acceptable, b) the use of technology in food and beverage café and restaurant services in Tarutung City still tends to be limited and low